Countering Extremism and Promoting Religious Tolerance: Exploring Interfaith Dialogue and Islamic Peacebuilding Initiatives - Almujahid Almujahid; Mudrik Mudrik; M.Ali Sodikin (Islamic Studies Journal (ISLAM), 2024)
This research explores how Islamic peace initiatives integrate traditional values ​​with modern strategies to counter extremism in multi religious societies. Using a Systematic Literature Review (SLR) approach that follows PRISMA principles, this research analyzes relevant literature from various academic databases to identify trends, practices and challenges related to Islam-based peace initiatives and interfaith dialogue. Key findings suggest that the integration of values ​​such as justice, peace, and compassion in modern conflict resolution strategies can increase the effectiveness of efforts to tackle extremism. In addition, this research identifies the important role of interfaith dialogue in building tolerance and reducing tensions between religious communities. While there are challenges to implementing peace initiatives, such as cultural and political barriers, there are also opportunities to increase interfaith collaboration and youth engagement. Practical recommendations for peace actors, ulama, and governments are provided to strengthen the effective implementation of peace initiatives.